Having, Being, and Doing Privilege: Three Lenses for Focusing on Goals in Feminist Classrooms - Daley, Kate M. (Atlantis)

(untitled) (Mount Saint Vincent University, 2015)
Using two published accounts of teaching experience in Women’s Studies classrooms by way of illustration, I argue that seeing privilege through three lenses—as something one has, something one is, and something one does—can assist feminist educators in meeting diverse goals in their anti-oppression classrooms as they continue to grapple with the messy and often contradictory challenges of privilege.